Biotechnological hydrogen production by photosynthesis. Issue 6 (21st August 2014) - Weber, Jost; Krujatz, Felix; Hilpmann, Gerd; Grützner, Sara; Herrmann, Jana; Thierfelder, Simone; Bienert, Georg; Illing, Rico; Helbig, Karsten; Hurtado, Antonio; Cuniberti, Gianaurelio; Mertig, Michael; et al.
<x xml:space="preserve">Abstract</x> Microbiological photosynthesis is a promising tool for producing hydrogen in an ecologically friendly and economically efficient way. Certain microorganisms (e.g. algae and bacteria) can produce hydrogen using hydrogenase and/or nitrogenase enzymes. However, their natural capacity to produce hydrogen is relatively low. Thus, there is a need to optimize their core photosynthetic processes as well as their cultivation, for more efficient hydrogen production. This review aims to provide a holistic overview of the recent technological and research developments relating to photobiological hydrogen production and downstream processing. First we cover photobiological hydrogen synthesis within cells and the enzymes that catalyze the hydrogen production. This is followed by strategies for enhancing bacterial hydrogen production by genetic engineering, technological development, and innovation in bioreactor design. The remaining sections focus on hydrogen as a product, that is, quantification via (in‐process) gas analysis, recent developments in gas separation technology. Finally, a discussion of the sociological (market) barriers to future hydrogen usage is provided as well as an overview of methods for life cycle assessment that can be used to calculate the environmental consequences of hydrogen production.